A child with a severe headache: Questions - Telhan, Leyla; Beğenik, Murat; Yaman, Yöntem; Yavaşcan, Önder (Springer, 2021)
A 12-year-old girl presented with complaint of severe headache lasting 10 days, nausea and vomiting for 1 day. The headache was localized in the right fronto-occipital region with spread to the neck and shoulders. In her medical history, tympanostomy tubes were inserted in her ears due to frequent otitis media with effusion before 2 years. She had recurrent reactive airway, asthma attacks, and allergic rhinitis. Before the definitive diagnosis could be established, she had received systemic antihistamine, nasal steroid, leukotriene antagonist, inhaler steroid, and salbutamol. She was treated with sefaclor per orally due to acute sinusitis for 5 days. The patient was admitted to our hospital with symptoms of severe headache. Physical examination showed that she was alert with an axillary temperature of 36.3 °C, weight of 60 (95th percentile) kg, height of 155 (65th percentile) cm, blood pressure of 150/100 mmHg (> 95th/> 95th percentile), and heart rate of 98 beats/min.
Keywords: Child; Headache; Sinusitis; Hepatosplenomegaly; Hypertension; Proteinuria; Hematuria